Salivary Alpha-Amylase as a Biomarker of Stress in Behavioral Medicine - Ali, Nida (Int J Behav Med, 2020)
In recent years, research in behavioral medicine has become increasingly focused on understanding how chronic and acute exposure to stress impacts health outcomes. During stress, the body’s physiological stress systems are activated. These systems closely interact with the immune system and are, thus, importantly implicated in the onset and maintenance of disease states. While much of the research in behavioral medicine that has investigated the effects of stress on disease has focused on the role of the hypothalamic-pituitary-adrenal axis and its downstream biomarker, cortisol, it is evident that the autonomic nervous system (ANS) also plays a crucial role in both the biological stress process and the manifestation and maintenance of stress-related symptoms. In recent years salivary alpha-amylase (sAA) has emerged as a valid and reliable marker of ANS activity in stress research and is therefore an important biomarker to consider in behavioral medicine. In this commentary, we will highlight research relevant for behavioral medicine that has utilized sAA measurements, both basally, and in response to stress, to examine ANS function in clinical populations. We will additionally summarize findings from studies that have examined the effects of various targeted interventions on changes in sAA levels. Through this, our aim is to present evidence that sAA can serve as a feasible biomarker of ANS (dys)function in health and disease. To this end, we will also highlight important methodological considerations for readers to keep in mind when including sAA assessments in their own studies. The overarching goal of this brief commentary is to highlight how a multidimensional approach toward physiological stress measurement can allow researchers to develop a better understanding of physical health and disease states.